Early Development of Chinese Sign Language in Shanghai Schools for the Deaf - Lin, Hao (Frontiers in Psychology, 2021)
The Shanghai variant of Chinese Sign Language (SCSL) is one of the main variants of Chinese sign languages, greatly influencing other sign languages, such as Hong Kong Sign Language and Singapore Sign Language. This paper is a first attempt to trace its origins and early history and deaf education in Shanghai until 1949. The data are collected in two ways: first, by delving into the archives, i.e. written records of deaf history and education in China during that time; second, by interviewing surviving deaf students who went to school before or around 1949. Our findings are as follows: a) SCSL began in the 1920s and emerged as a distinct sign language in the 1940s. Two deaf schools were the power shaping its progress among several deaf schools established in Shanghai: Fryer deaf school and Group learning deaf school. The sign variants of these two schools form the backbone of SCSL. b) Deaf teachers are one of the key factors that affect the early development of sign language. Chinese deaf played a vital role in the rise and spread of SCSL in the 1930s and 1940s, as some deaf teachers opened deaf schools in Shanghai and other cities, even other countries or areas, thus helping SCSL to spread. c) SCSL is characterized by traces of foreign sign languages, especially ASL, due to language contacts linked to deaf education at that time, e.g. some proper names, like XUJIAHUI, SHANGHAI1 and some high-frequency words. d) However, foreign sign languages’ direct influence is negligible due to the lack of participation of deaf foreigners in deaf education in Shanghai and oralism advocated by foreign educators in relevant deaf schools. To sum up, deaf teachers for deaf schools are key to the early development and spread of SCSL.